Polymicrobial Bacteremia Involving Comamonas testosteroni - Jose Orsini; Eric Tam; Naomi Hauser; Salil Rajayer (Case Reports in Medicine)
Comamonas spp. are uncommon isolates in microbiology laboratories and have been rarely observed as an infectious agent in clinical practice. They have widespread environmental distribution and have been isolated from water, soil, and plants as well as from some hospital devices such as intravenous catheters and water contained in humidifier reservoirs used in respiratory treatment. The genus Comamonas originally contained the following species: acidovorans, testosteroni, kerstersii, terrigena, denitrificans, and nitrativorans. It now contains 17 species, while acidovorans spp. have been reclassified as Delftia acidovorans. In spite of its uncommon human pathogenesis, there are few reports on the aggressive manner of it as an opportunistic pathogen, mostly related to testosteroni spp. We present a case of polymicrobial bacteremia involving Comamonas testosteroni. The aim of this case report is to alert clinicians to the potential diagnosis of bloodstream infections caused by uncommon pathogens.